An assessment of mode of delivery in history indicated versus ultrasound indicated vaginally placed cervical cerclage. (March 2017) - Story, Lisa; Shennan, Andrew
Abstract: Objective: Treatment modalities to reduce the incidence of preterm birth are currently limited. Cerclage, is a common and established intervention in most obstetrics units worldwide, however, many questions regarding its efficacy, with respect to pregnancy outcomes remain unanswered. This study aims to investigate whether an antenatal placed cerclage affects the subsequent mode of delivery in women at high risk of preterm birth who labour. Study design: A retrospective case controlled study was performed at St Thomas's Hospital London. Women who had undergone cervical cerclage were identified using a pre-existing database (n = 152). Cases were excluded where a C-section had been performed prior to labour (n = 26), datasets were incomplete (n = 5) or a rescue cerclage was performed (n = 2). Remaining cases were categorised into those who had: history indicated (n = 68) or ultrasound indicated (n = 51) cerclage. Control cases were obtained from the same database who also laboured but had not undergone cerclage, matched according to gestational age at delivery and parity (n = 114). Demographic details and outcome data were recorded. Groups were compared using Chi Squared analysis for discrete variables and t -test for continuous variables using IBM SPSS Statistics version 22. Results: There was no statistical difference in the emergency C-section rate between history indicated and ultrasound indicated cerclage, or between patients who received cerclage and those who had not (p = 0.592). The emergency C-section rate for each group was: history indicated, 25%, ultrasound indicated 18% and no cerclage 18%. Conclusions: Women at risk of preterm birth have high rates of emergency C-section despite the fact that the majority were multiparous. However, they can be reassured that cervical cerclage does not increase this risk.